STRUCTURAL AND TYPOLOGICAL FEATURES UNITS OF THE RUSSIAN TERMINOLOGICAL SYSTEM OF THE OIL AND GAS INDUSTRY - Al-Sultany, Methaq Mohammed Ismael; Abbas, Ahmed Fadil (Al-Adab Journal, 2022)
The article is devoted to the classification based on the thematic principle of the units of the Russian terminological system of the oil and gas industry and the peculiarities of the functioning of terms in different types of discourse. As a result, the author's typology of terms in the oil and gas sector is presented, examples are given that reflect the functioning of terms in the communicative space of scientific and mass-media discourses.